2019
DOI: 10.3390/ijms20092358
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Dysfunction as Determinant of Obesity-Associated Metabolic Complications

Abstract: Obesity is a critical risk factor for the development of type 2 diabetes (T2D), and its prevalence is rising worldwide. White adipose tissue (WAT) has a crucial role in regulating systemic energy homeostasis. Adipose tissue expands by a combination of an increase in adipocyte size (hypertrophy) and number (hyperplasia). The recruitment and differentiation of adipose precursor cells in the subcutaneous adipose tissue (SAT), rather than merely inflating the cells, would be protective from the obesity-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
789
0
35

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,073 publications
(835 citation statements)
references
References 182 publications
(237 reference statements)
11
789
0
35
Order By: Relevance
“…Obesity pathogenesis involves infiltration of macrophages into expanding adipose tissue and both activated macrophages and hypertrophic adipocytes contribute to local low-grade inflammation in adipose tissue and abnormal hepatic lipid metabolism [66]. Studies have previously demonstrated that animals on HF diets showed chronic inflammation in white adipose tissue and ectopic fat deposition in the liver, which was associated with increased expression of hepatic PPARγ as a transcription factor essential for adipocyte differentiation [67].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity pathogenesis involves infiltration of macrophages into expanding adipose tissue and both activated macrophages and hypertrophic adipocytes contribute to local low-grade inflammation in adipose tissue and abnormal hepatic lipid metabolism [66]. Studies have previously demonstrated that animals on HF diets showed chronic inflammation in white adipose tissue and ectopic fat deposition in the liver, which was associated with increased expression of hepatic PPARγ as a transcription factor essential for adipocyte differentiation [67].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-driven changes of the adipose tissue monocytes/macrophages alters the secretion of proinflammatory cytokines which contributes to the progression of inflammation and the development of insulin resistance (19,20). Tumor necrosis factor-α (TNF-α), which is overexpressed in obese humans and rodents, plays a central role in metabolic inflammation and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue can expand either by hypertrophy or hyperplasia [19]. On the one hand, hypertrophy of adipocytes can increase hypoxia and mechanical stress to neighboring cells and the extracellular matrix, resulting in decreased adipose tissue function, which contributes to the early onset of metabolic disease, and persistently elevated levels of nutrients in the blood, which cause toxic lipid deposits in other tissues, such as muscle and the liver [20,21]. On the other hand, hyperplastic growth is considered to be a healthy and adaptive mechanism by which to maintain proper vascularization, responses to anti-inflammatory hormone adiponectin, and insulin-sensitizing and other metabolism-modulatory adipokines [20,22].…”
Section: Discussionmentioning
confidence: 99%